Ghost twerkers : a play - Akinola, Ola-Kris (My University, 2018)
This play is a response to the increase in rape and femicide cases in South Africa around 2018. It creates an opportunity to increase awareness, educate, inform as well as initiate dialogues on gender based violence (GBV) in order to interrogate and, perhaps, stem the scourge in the country, continent and the world. This responsibility is owed by all of humanity, for all of humanity.
A play
Keywords: Gender based violence; Human rights violation; Rape; Femicide; Women -- Violence against -- South Africa; Rape victims -- South Africa; Women -- Crimes against -- South Africa; Human rights -- South Africa